Concurrent coverage and determinants of vitamin A supplementation and deworming among children aged 12–59 months in 15 Sub-Saharan African countries - Thomas Kidanemariam Yewodiaw; Mequanint Dessie Bitewa; Abiyu Abadi Tareke (PLoS ONE, 2026)
Background Vitamin A supplementation (VAS) and deworming (DW) are proven, cost-effective interventions that protect children against preventable morbidity, mortality, and the burden of micronutrient deficiencies and parasitic infections. Nevertheless, many children fail to receive both interventions simultaneously, limiting the potential health gains. Assessing co-coverage and its determinants is crucial for guiding integrated child health strategies and closing persistent gaps across Sub-Saharan Africa. Methods We analyzed DHS data from 15 Sub-Saharan African countries, including 107,725 children aged 12–59 months. The primary outcome was co-coverage of vitamin A supplementation and deworming within six months. Weighted descriptive statistics and mixed-effects logistic regression assessed determinants at individual, household, community, and country levels, accounting for survey design and clustering. Variables with p < 0.20 or deemed theoretically relevant were included in the multilevel model (p < 0.05, 95% CI). Results The pooled co-coverage of vitamin A supplementation (VAS) and deworming (DW) among children aged 12–59 months was 44.0% (95% CI: 43.4–44.6%), despite individual coverage of 57.1% for each intervention. Approximately 13% of children received either Vitamin A or deworming as a single intervention. Nearly 30% of children received neither intervention. Co-coverage was lowest in Sierra Leone (10.3%) and Gabon (13.2%), moderate in Burkina Faso (28.6%), Côte d’Ivoire (31.0%), Mozambique (44.0%), and Tanzania (44.7%), and highest in Lesotho (58.4%) and Rwanda (84.7%). Vitamin A supplementation coverage was lowest in Gabon (15.7%), Sierra Leone (16.5%) and highest in Rwanda (89.1%) and Lesotho (73.6%), while deworming alone was lowest in Sierra Leone (30.3%) and Burkina Faso (36.7%) and highest in Rwanda (89.4%) and Lesotho (62.4%). Co-coverage of vitamin A supplementation and deworming was higher among children aged 24–47 months (AOR = 1.07), fully immunized children (AOR = 1.41), and those with older, educated mothers who attended antenatal care (AORs 1.14–1.59) or had media exposure (AOR = 1.13). Household wealth also increased the likelihood (AORs 1.27–1.64), while urban residence reduced it (AOR = 0.84). At the country level, compared with Burkina Faso, Rwanda (AOR = 20.05), Mauritania (AOR = 4.30), and Lesotho (AOR = 3.92) had the highest odds, whereas Gabon (AOR = 0.36) and Sierra Leone (AOR = 0.22) had the lowest inter-country disparities in integrated child health coverage. The intraclass correlation coefficient (ICC) indicated that approximately 21.6% of the variance in concurrent coverage was attributable to between-country differences. Conclusion Co-coverage of vitamin A supplementation and deworming in 15 sub-Saharan Africa countries is low, with only 44% of children aged 12–59 months receiving both interventions, far below the WHO 80% target. Coverage varied widely, with Rwanda leading and Sierra Leone and Gabon lagging. Strengthened harmonized campaigns, routine service integration, and targeted outreach are essential to improve equitable child health outcomes.